2018
DOI: 10.1016/j.vacuum.2018.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weld parameters on porosity formation in electron beam welded Zircaloy-4 joints: X-ray tomography study

Abstract: Zircaloy-4 to Zircaloy-4 (Zr-4) similar butt joints were prepared using Electron Beam Welding (EBW) technique under different weld conditions such as with beam oscillation, without beam oscillation and at different welding speeds. Three-dimensional (3D) visualization of porosity in weld joints was carried out using X-ray computed tomography (XCT) technique. Quantification of porosity such as the average size, number and shape of the pores were evaluated and compared among weld joints produced under different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…During solidification, bubbles do not have time to leave the weld pool and turn into pores, so larger weld pool and slow cooling are beneficial for low porosity. For high intensity beam welding processes, such as laser welding and electron beam welding, it has been proven that reducing the welding speed can reduce the porosity [237]. For arc welding, Wiesner et al [87] demonstrated that a lower welding speed was also effective in reducing porosity during welding of aluminium castings, and it could eliminate more gas pockets from the weld pool, which lowered the quantity of pores in the weld bead.…”
Section: Porositymentioning
confidence: 99%
“…During solidification, bubbles do not have time to leave the weld pool and turn into pores, so larger weld pool and slow cooling are beneficial for low porosity. For high intensity beam welding processes, such as laser welding and electron beam welding, it has been proven that reducing the welding speed can reduce the porosity [237]. For arc welding, Wiesner et al [87] demonstrated that a lower welding speed was also effective in reducing porosity during welding of aluminium castings, and it could eliminate more gas pockets from the weld pool, which lowered the quantity of pores in the weld bead.…”
Section: Porositymentioning
confidence: 99%
“…The tensile properties of Zr-4 alloy electron beam welded joints are not inferior to those of the parent material [ 19 ], but the presence of pores in the weld may affect the corrosion performance of the joint [ 20 ]. Bandi et al [ 21 ] demonstrated through Raman spectroscopy that the pores in the Zr-4 electron beam welded joint are mainly hydrogen pores. Zhang et al [ 22 ] found that the EBW joint of Zr-702 alloy is composed of α-Zr and β-Zr, and β-Zr small blocks are distributed along the edges of layered α-Zr, which indicates that the joint has better corrosion resistance than the BM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have suggested the use of beam oscillation to reduce porosity formation. XCT and Raman spectroscopy has been performed by Bandi et al [15] to investigate micro-porosity during EBW of Zircaloy-4 alloys. They have also reported a significant reduction in porosity by using an oscillating beam.…”
Section: Introductionmentioning
confidence: 99%